Why not Activated? The Temporary Protection Directive and the Mystery of Temporary Protection in the European Union - (:unkn) unknown (My University, 2019)
Following the conflicts in former Yugoslavia, temporary protection was introduced as a crucial elementof the European Union’s (EU) response to refugee crises. The EU even adopted a directive, the TemporaryProtection Directive, regarding its implementation. However, despite several refugee crises, it was notactivated. Building on a comprehensive analysis of official documents of European institutions andthe available secondary literature, this article investigates the main reasons behind its inactivation. Itreveals that the real concerns of EU Member States lay in the measures promoting a balance of efforts toprovide temporary protection. In other words, Member States’ concerns over responsibility and burdensharing cast a shadow over temporary protection in the EU. The article concludes that the Directive’sinactivation indicates a crisis of fundamental principles in European integration.

Geçici koruma, Yugoslavya’daki çatışmaların ardından Avrupa Birliği’nin (AB) mülteci krizleri karşısında yürürlüğe koyacağı uygulamaların en önemli unsuru olarak ilan edildi. AB, uygulanmasına ilişkin bir ‘Geçici Koruma Yönergesi’ bile kabul etti. Ancak, bu zamana kadar yaşanan birkaç mülteci krizine rağmen, bu yönerge yürürlüğe konmadı. Avrupa kurumlarının resmi belgelerinin ve mevcut ikincil literatürün kapsamlı bir analizini temel alan bu makale, bu yönergenin yürürlüğe konmamasının ardındaki temel nedenleri araştırmaktadır. Makaleye göre, AB üye devletlerinin gerçek kaygıları, geçici koruma sağlama çabalarının dengesini destekleyen tedbirler konusunda yoğunlaşmaktadır. Başka bir deyişle, AB’de geçici koruma, üye devletlerin sorumluluk ve bütçe paylaşımı konusundaki endişelerinin gölgesi altında kalmaktadır. Makale, yönergenin yürürlüğe konmamasının Avrupa bütünleşmesinde bir temel ilkeler krizini gösterdiğini belirterek son bulmaktadır.
Neden Yürürlüğe konmadı? Geçici Koruma Yönetmeliği ve Avrupa Birliği’nde Geçici Koruma’nın Gizemi
Keywords: Uluslararası İlişkiler; Siyasi Bilimler